DMAIC methodology application in bakery for French bread-quality standardization purposes - Cicalé, Vinicius Suedan; Marfil, Paulo Henrique Mariano (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
French bread is one of the food items mostly consumed in Brazil, as well as Brazilian bakeries’ core product. Its growing demand forces bakeries to adopt strategies to speed up the production of Brazilians’ “favorite”, without losing its typical taste and quality. The current study was carried out in a traditional bakery in Araraquara City, São Paulo State. Its aim is to reduce the number of non-conformities in the French bread-production process. The DMAIC cycle was herein adopted as main methodology, although other tools, such as data collection and analysis, brainstorming and Pareto charts, 5W1H and risk mapping, were also used. Results have evidenced that more than 50% of the investigated production was not in compliance due to labor issues, raw material type and the adoption of non-standard processes. Finally, an action plan comprising bakery-intervention proposals was prepared and it evidenced the need of standardizing the used chemical yeast, of training the bakery’s employees and of standardizing the time of each production stage.